Differences in sensory-motor cortex activation patterns during level and stair walking in patients with knee osteoarthritis: protocol for a cross-sectional study - Deng, Qian; Jin, Guohua; Lou, Xia; Ding, Yuwu; Xu, Haichen; Yang, Kun; Liu, Bingli; Jiang, Liming (Frontiers in Aging Neuroscience, 2025)
BackgroundKnee osteoarthritis (KOA) is a chronic degenerative disease characterized primarily by pain and joint dysfunction, especially during level and stair walking. Although traditionally classified as a peripheral joint disease, emerging evidence implicates central nervous system (CNS) abnormality in KOA pathogenesis. Our previous studies found that KOA patients showed decreased activation in sensory-motor cortex during isolated joint movements. However, it is not yet clear how brain activation patterns change during level and stair walking. Therefore, this study will investigate the sensory-motor cortex activation in KOA patients during different walking environments, providing evidence for potential targets for KOA central interventions.MethodsThis study is designed as a cross-sectional observation, aiming to recruit 20 KOA patients and 20 demographically similar healthy controls (HC). Functional near-infrared spectroscopy (fNIRS) is utilized to assess the hemodynamic responses in the cerebral cortex within the specified regions of interest (ROIs), including the primary somatosensory cortex (S1), primary motor cortex (M1), and somatosensory association cortex (SAC). These measurements will be taken during three motor tasks: level walking, ascending stairs, and descending stairs. Simultaneously, surface electromyography (sEMG) is employed to measure muscle activity of the key muscle groups around the knee joint. The VAS and the WOMAC used to evaluate pain and functional symptoms in KOA patients, respectively. Subsequently, the potential correlations between cerebral hemodynamics changes within ROIs and clinical indicators are analyzed.DiscussionThis study, based on “differential activation of the sensory-motor cortex under movement,” innovatively observes the relationship between pain and functional impairment in KOA patients and activation levels in specific brain regions across different motor environments. This not only provides a basis for early prediction of KOA onset but also offers potential targets for clinical interventions in KOA. Ultimately, the results of this study may open new perspectives for the rehabilitation of chronic musculoskeletal diseases.